Isolated Thoracoschisis: Case Report and Review of Literature - Seleim, Hamed Mahmoud; ElFiky, Mahmoud M.A.; Fares, Ahmed E.; Elbarbary, Mohamed M. (European Journal of Pediatric Surgery Reports, 2015)
A full-term male baby presented at day 2 postnatal with Riedel liver lobe, stomach, and much of the bowel herniating through a thoracic wall defect located just above and lateral to the left nipple. Operative conversion into a gastroschisis-like defect with construction of a silo bag was done. On thorough review of literature, it was found that this is only the second male infant reported with isolated thoracoschisis.
Keywords: thoracoschisis; gastroschisis; silo; limb–body wall complex